Affetti e inconscio - Scacco, Elena (Il sogno della farfalla, 2014)
The article describes a lesson held at a high school in Rome. As part of a project of the “Amore e Psiche” Association, the lesson explored issues like drug abuse, sexuality and affects as experienced in the delicate period of puberty. By illustrating terms such as “identity”, “desire” and “refusal”, and taking intriguing cues from books and cinema, the author offers a simple and linear description of the mental development during puberty and its failures.